FACTORS AFFECTING CONSUMER BEHAVIOR IN DECISION MAKING PURCHASE PRODUCT BRAND WATCHES GUESS (CASE STUDY AT. GILANG AGUNG PERSADA, SHOWROOM GUESS MALIOBORO MALL YOGYAKARTA) - MUGIANI, ERY (Management, 2010)
The study titled Factors Affecting Consumer Behavior Decision Making Purchase Product Brand Watches Guess Guess at Malioboro Mall Yogyakarta Showroom held in January to March of 2010 with respondents Guess Showroom Visitors Malioboro Mall Yogyakarta during January to March 2010. This study aims to determine and analyze: (1) whether the factors Promotion, Price, Models and material effect on decisions to buy products at the Guess brand watches Guess Showroom Malioboro Mall Yogyakarta. Data collection methods used are questionnaires with data analysis method used is deskriptive and quantitative analysis method is by measurement methods that can be expressed in terms of numbers. Based on the analysis of multiple linear regression equation with t test results can be seen that the promotional factors influencing consumers in making product purchasing decisions Guess brand watches with t calculate the size of the t table (3.852 > 1984), the price factor influencing consumer purchasing decisions at the product Guess brand hand with t calculate the size of the t table (5.605 > 1.984), the model factors influencing consumers in making product purchasing decisions Guess brand watches with t calculate the size of the t table (1.996 > 1984) and for material factors affecting consumer product purchase decision Guess brand watches with t calculate the size of the t table (2.017 > 1.984). In calculating the F test results also can be seen that the promotional factors, pricing, models and materials jointly affect product purchase decision Guess brand watches in the Guess Showroom Malioboro Mall Yogyakarta with calculated F value is greater than F table (15.047 > 3.089). Among the variables tested was the price factor Guess brand watches the most influence on purchase decisions Guess brand watches in the Guess Showroom Malioboro Mall Yogyakarta in January to March of 2010 with a beta coefficient of 0.810 larger than the promotion of factors that have a value of 0.316 factor Models with a value of 0.128 and 0.211 with the value of material factor. Simultaneously the product purchase decision Guess brand watches in the Guess Showroom Malioboro Mall Yogyakarta in January to March of 2010 is influenced by the Promotion, Price, Models and Materials with a regression coefficient of 0.848 or equal to 0.152 or 84.8% while at 15 , 2% influenced by other variables not included in this study Keyword : Behavior, Watch, Brand